Peningkatan Nilai Ekonomis Batik Tulis dari Daun Sirih (Batik D’Suru) - Andri Harmoro Kusumo Broto; Sofyan Mahardika Rahardi; Mega Andriana Jane; Kinanti Ayu Wigaringtyas; Abdullah G Toda; Ndaru Handian Dhuhava; Rusbiyanti Sripeni (JURNAL DAYA-MAS, 2018)
Batik is a picture art that is poured in a piece of cloth that is one of the Indonesian nation's identity that is recognized as World heritage. Unesco has set Batik as a Masterpieces of the Oral and the Intangible Heritage of Humanity on October 2, 2009. In Indonesia, Batik has expanded and penetrated the market share as the development of fashion in the world. Motives that exist in the market is also various types and apparently. Among others: Batik Mega Mendung, Batik Parang Rusak, Batik Kawung, etc. Which makes each type of batik has a different aesthetic value is different its uniqueness.. Dyeing techniques also vary from dyeing techniques, connective techniques, jumputan techniques etc.. Seeing this opportunity encourages the emergence of the idea of making Batik, but replace the use of the night with Leaf Betel. Leaf Betel itself is only used as medicine or herbal medicine by the surrounding community. With this idea, in addition to raising the economic value of Leaf Betel, the original legacy of Indonesia can also be preserved. Starting from drawing sketches on mori cloth, then burst the Batik motif with Scratches Ginger Leaf Betel on it using Nails. After this step is passed, continued the coloring, for staining time required about 1-2 hours for 1x1 meter sized fabric. The results are sold in the form of batik cloth, and marketed through social media, and sold directly in the area of Madiun and surrounding areas.